An electric motor thermal management system for hybrid vehicles: modelling and control. Issue 3 (2016) - Tao, Xinran (William); Zhou, Kan; Wagner, John R.; Hofmann, Heath
The HEV e-motor's internal temperature significantly influences its torque/power capabilities. The dominant heat sources are located within the e-motor stator windings and create 'hot spots'. To keep the motor functioning properly without exceeding the established temperature limits, a new cooling concept for PM e-motors featuring advanced controllers is proposed. Firstly, a reduced-order finite element model describes the e-motor's thermal behaviour. Next, an optimal regulator calculates the ideal (target) heat removal rate at its cooling surface. Lastly, a nonlinear tracking controller governs the cooling system operation. Numerical simulation has been conducted to validate the cooling concept. In the urban assault cycle, the stator hot-spot temperature is stabilized with an average error of 0.13°C and a 68% power consumption reduction achieved when compared to classical control. Similarly, the cooling system power consumption is reduced by 28.9% with the proposed controllers for the convoy escort driving cycle.